The relation between salivary sIgA level and caries incidence in Down syndrome children - Rosdiana Rosdiana; Mochammad Fahlevi Rizal (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2012)
Background: Down syndrome or Trisomy 21 is a genetic disorder caused by extra chromosome on chromosome 21. Down syndrome child, however, has good resistance against caries, and some of them even are caries-free. It is because the level of salivary sIgA in Down syndrome children is equal or even higher than that in normal children. Purpose: This review was aimed to review the relation between salivary sIgA level and caries incidence in Down syndrome children. Reviews: Down syndrome is a collection of symptoms caused by chromosomal abnormality that has a number of physical and mental disorders. Down syndrome children, nevertheless, have significantly lower incidence of caries than normal children. These conditions are thought to relate to characteristics of oral cavity and the level of salivary sIgA in Down syndrome children. Caries is a disease of dental hard tissues caused by the fermentation of sucrose into glucans by glucosyltransferase enzymes (GTF) of Streptococcus mutans (S. mutans). One of proteins in saliva that acts as a defense mechanism is imunoglubulin. Secretory immunoglobulin A (sIgA) inhibits the activity of S. mutans as bacteria causing caries forming glucan. This immunoglobulin, sIgA, is the most abundant immunoglobulin in saliva. The level of salivary sIgA in Down syndrome children is significantly higher than that in normal children. Conclusion: Besides factors of tooth eruption delays, wide spaces among teeth, microdontia, pH, and high saliva contents (calcium, sodium, bicarbonate), the low incidence of caries in Down syndrome children is also related with the higher level of salivary sIgA in Down syndrome children than that in normal children.Latar belakang: Sindroma Down atau Trisomi 21 merupakan kelainan genetik yaitu adanya kromosom ekstra pada kromosom 21. Anak sindroma Down memiliki resistensi yang baik terhadap karies dan sebagian dari mereka bebas karies. Kadar sIgA saliva anak sindroma Down sama atau bahkan lebih tingi dari anak normal. Tujuan: Tujuan dari tulisan ini adalah mencari hubungan antara kadar sIgA di dalam saliva dengan kejadian karies pada anak sindroma Down. Tinjauan pustaka: Sindroma Down adalah suatu kumpulan gejala akibat abnormalitas kromosom yang memiliki sejumlah kelainan fisik dan mental. Anak sindroma Down secara signifikan memiliki prevalensi karies yang lebih rendah jika dibandingkan anak normal. Kondisi ini diduga berhubungan dengan karakteristik rongga mulut dan kadar sIgA saliva anak sindroma Down. Karies merupakan penyakit jaringan keras gigi yang disebabkan oleh fermentasi sukrosa menjadi glukan oleh enzim glucosyltransferase (GTF) dari Streptococcus mutans (S. mutans). Salah satu protein di dalam saliva yang berperan sebagai mekanisme pertahanan adalah imunoglubulin. Imunoglobulin A sekretori (sIgA) berperan menghambat aktivitas S. mutans sebagai kuman penyebab karies membentuk glukan. sIgA adalah imunoglobulin yang paling banyak terdapat pada saliva. Kadar sIgA saliva sindroma Down signifikan lebih tinggi dibandingkan anak normal. Kesimpulan: Rendahnya insiden karies anak sindroma Down berhubungan dengan kadar sIgA di dalam saliva anak sindroma Down yang lebih tinggi dibandingkan anak normal selain faktor keterlambatan erupsi gigi geligi, ruang antar gigi yang lebar, mikrodonsi, pH dan kandungan saliva (kalsium, sodium, bikarbonat) yang tinggi.